2020
DOI: 10.3390/molecules25225342
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin and its Effects in Inflammatory Responses and Inflammation-Associated Diseases: Recent Advances and Future Directions

Abstract: Astaxanthin is a natural lipid-soluble and red-orange carotenoid. Due to its strong antioxidant property, anti-inflammatory, anti-apoptotic, and immune modulation, astaxanthin has gained growing interest as a multi-target pharmacological agent against various diseases. In the current review, the anti-inflammation mechanisms of astaxanthin involved in targeting for inflammatory biomarkers and multiple signaling pathways, including PI3K/AKT, Nrf2, NF-κB, ERK1/2, JNK, p38 MAPK, and JAK-2/STAT-3, have been describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 83 publications
(94 reference statements)
1
91
1
Order By: Relevance
“…The inflammatory response has a close relationship with many diseases. [43][44][45][46] As the important part of immune system, it is viewed as a driving factor causing changes in neurocircuits and neurotransmitters, which are closely related to the onset of depressive symptoms. Mounting evidence has solidified the relationships between depression and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response has a close relationship with many diseases. [43][44][45][46] As the important part of immune system, it is viewed as a driving factor causing changes in neurocircuits and neurotransmitters, which are closely related to the onset of depressive symptoms. Mounting evidence has solidified the relationships between depression and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…While nowadays, knowledge on this topic in salmon is scarce; the effect of Ax on the inflammatory response related to human diseases has been the subject of attention of many studies. Amar et al (2012) and Chang and Xiong (2020) have shown that Ax increased the protection of rainbow trout challenged with infectious hematopoietic necrosis virus. The authors hypothesized that Ax may influence the resistance of rainbow trout to viral pathogen via inhibition of virally induced and ROS-mediated oxidative stress.…”
Section: Effect Of Astaxanthin On Pylorus Of Post-smolt Salmon (+ Ax Vs − Ax)mentioning
confidence: 99%
“…However, the support given by exogenous molecules seems fundamental, especially as age progresses. Although some animal-derived antioxidants such as vitamin A and the anti-inflammatory carotenoid astaxanthin also exist [ 20 ], these molecules, including some vitamins, both hydro- (vitamin C) and fat-soluble (vitamin A in precursor forms and vitamin E) ones, carotenoids, polyphenols and various flavonoids, are all derived from vegetable sources [ 21 ]. It should, nevertheless, be taken into account that when used as exogenous supplements, antioxidants could reach supraphysiological doses that are capable of producing detrimental rather than beneficial effects, thus increasing the oxidative stress status.…”
Section: Introductionmentioning
confidence: 99%